The Social Construction of Scabies Disease Among Islamic Boarding School Students - Suryanto, Totok Agus; Ladylie, Ladylie (IJIBS, 2024)
The social construction of scabies among Islamic boarding school students (santri) is a critical yet underexplored issue. Previous studies have not fully addressed how scabies is perceived and constructed within this community. This study focuses on understanding the meanings and social interactions surrounding scabies among santri. Using a qualitative exploratory descriptive approach, data were collected through participant observations, in-depth interviews, and documentation studies. Analysis involved data interpretation, display, and conclusion withdrawal, guided by Berger and Luckmann's theory of social construction, which includes externalization, objectivation, and internalization. The findings reveal diverse meanings attached to scabies among santri, including "santri stamp," "legitimate," "grace and favors," "blessing entrance," "routine disease," and "the value of togetherness." These meanings stem from social prestige and collective subjectivity shaped by the roles and statuses within the boarding school environment. The social construction of scabies among santri is maintained through the ongoing willingness of social agents to adhere to daily activities that reinforce existing social constructions. This study highlights the importance of understanding health conditions' social meanings within specific cultural contexts, significantly impacting community responses and management strategies.